2015
DOI: 10.1108/jmhtep-02-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Learning from service user and carer involvement in clinical psychology training

Abstract: Purpose – The purpose of this paper is to build a theoretical model of how and what clinical psychologists learn from service user and carer involvement in their training. Design/methodology/approach – A qualitative research design was adopted, and verbatim transcripts of semi-structured interviews conducted with 12 clinical psychologists were analysed using grounded theory methodology. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Rush (2008) proposes that the emotion aroused by the impact of the personal story leads directly to reflection and attempts to make sense of the experience. For Schreur et al (2015), reflection is also promoted by the emotion produced by hearing the personal story. In all three models, role change is also present and in both Schreur et al ’s model and the model developed here, there is an importance placed on novelty or uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rush (2008) proposes that the emotion aroused by the impact of the personal story leads directly to reflection and attempts to make sense of the experience. For Schreur et al (2015), reflection is also promoted by the emotion produced by hearing the personal story. In all three models, role change is also present and in both Schreur et al ’s model and the model developed here, there is an importance placed on novelty or uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Rush (2008) proposes that attitude change precedes resolving to take action and then taking action. Schreur et al (2015) conceptualise increased awareness of and motivation to engage with service user issues as one of the positive outcomes of the reflective process. There are clearly processes that occur in the room that lead to changes in attitude straight away.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these difficulties, research does show that involving service users in the training of clinical psychologists can positively impact trainees’ learning and attitudes, such that the “us and them” barrier is broken down (Harper et al ., 2003), awareness of service users’ perceptions of services are increased (Tickle and Davison, 2008) and academic learning moves into the “real life” domain (Schreur et al ., 2015). However, each of these studies focusses on the trainee/student experience and does not report on the experience of involvement from the service users’ perspective.…”
Section: Introductionmentioning
confidence: 99%
“…This could also incorrectly imply that service users are a homogeneous group. Research into clinical psychology training found that increased contact between mental health professionals and service users in the context of equal status may reduce stigmatic cognitive separations of 'us' and 'them' (Schreur, Lea, and Goodbody 2015). Moore acknowledges the progress made in service user involvement as a whole and suggests changes which could increase the value of their input and reduce the risk of tokenism.…”
mentioning
confidence: 99%